Computing Human Identity in Greg Egan’s Permutation City. - Camara, Anthony (Western Humanities Review)
A literary criticism of the book "Permutation City" by Greg Egan is presented. It examine its provocative re-imagining of humanism; mentions the human subject as an open-ended engineering project that necessitates continual revisionary technological interventions; and also mentions that brain scanning and instantiating duplicate virtual reality (VR) bodies are crucial technologies of replication necessary for the creation of copies in the novel.